ASPECTS OF SELECTING THE METHODOF RESTORATION OF THE VITAL FRONTAL GROUP TEETH IN MODERN CONDITIONS (LITERATURE REVIEW) - O. I. Lobach; N. V. Lapina (Сеченовский вестник, 2018)
The wide range of materials and methods for restoration the shape and function of the frontal group of teeth appeared due to modern technology in the daily practice of a dentist. The defeat of the aesthetic region of the tooth (especially the vestibular surface) leads to suffering, self-doubt and a decrease in the patients quality of life. In this regard, the doctor bears a high degree of responsibility, and must decide on a method of recovery and choice of material. In modern aesthetic dentistry, polymerizable composite materials are the method of choice when filling the lost volume of hard tissues of vital teeth. Russian materials deserve special attention in the current political and economic situation in our country. A review of the literature showed the need for a detailed study of the properties of composites in the oral cavity for a qualitative selection of the optimal variant both for physical characteristics and for financial accessibility.